EFEKTIVITAS PROGRAM PERTUKARAN PEMUDA INDONESIA-KANADA DALAM MENINGKATKAN AKTIVITAS KEPEMUDAAN DI PROVINSI KALIMANTAN TIMUR - Alfi Febriansyah (Jurnal Administrative Reform, 2020)
The purpose of this research is to determine the effectiveness of Indonesia-Canada Youth Exchange Program in Kalimantan Timur in order to increase youth activity, primary data were obtained through key informant namely Committee from Dinas Pemuda dan Olahraga Kalimantan Timur, and 4 informants consisting of PCMI Kalimantan Timur, also alumnae of Indonesia-Canada Youth Exchange Program from Kalimantan Timur Province, also supported by secondary data which is relevant archive. Furthermore, it was analyzed using Analysis Qualitative Data with CIPP Model through the scheme of FAO/Soekartawi evaluation research activities. The result of the research shows that the Indonesia-Canada Youth Exchange Program in Kalimantan Timur is not effective to increase youth activity because in implementation is founded that some components of program success factor were not implemented.Keywords: Effective, Youth Exchange, CIPP